Factors Influencing Head Teacher's Leadership: A Case of Community School in Kathmandu Valley - Sherpa, Dawa; Baraily, Khagendra (Education and Development, 2020)
This study aimed to explore the factors influencing leadership of head teacher. For this purpose, interpretative phenomenology was employed. Five head teachers having more than ten years' experience in different community secondary schools of Kathmandu valley were selected as participants for their lived experience and perception through purposive sampling. Information was collected through participants by in-depth interviews and semi-structured questionnaire to draw the perception and experience of the participants. In interviews, we attempted to interpret respondents' explanations, experiences, struggles, and evidences related to head teacher. Interviews were transcribed as verbatim and coded to generate themes. Themes were analyzed with reference to the essence of transformative leadership theory to reach in conclusion. The study finding showed that size of organization, level of interaction, decision making skill, problem solving skills, and team efforts are influencing factors for effective leadership. Head teacher’s leadership can be positively influenced in small organization but professional development of staffs can be negatively impacted. Frequent collaboration among stakeholders and interpersonal relationship among staff influences the leadership of head teacher positively. The tactful leadership skills for problem solving inspired the head teacher to strengthen the capacity of the organization along with team effort. Thus, the leadership of head teacher in community school needs to be sensitized to apply appropriate size based on stakeholder. The intensity of collaboration is required to be maintained with the principles of rich communication and team effort.